2010
DOI: 10.4314/lwati.v7i1.57478
|View full text |Cite
|
Sign up to set email alerts
|

Intonation and Attitude in Nigerian English

Abstract: Intonation is an important phenomenon in language believed to have strong effect on communication. It is often said in reference to the primacy of intonation meaning over lexical content that "It's not what you said, it's how you said it!". To this effect, a number of scholars have argued that intonation conveys different attitudes in English and is principally responsible for misunderstandings between native and non-native English speakers. This paper, therefore, attempts to ascertain the extent to which Nige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…It was observed that the use of tunes in Nigerian English was low; where the differences lie minimally in the utterances with falling pitch and appear significantly with the rising tone. Akinjobi and Oladipupo (2010) also looked at the place of intonation as not only being that which is said but how it is said, investigating the intonation and attitude in Nigerian English with the intention of ascertaining the extent to which Nigerian speakers of English use English intonation tunes to express attitudes. A level of deficiency in the use of intonation was recorded among the respondents.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It was observed that the use of tunes in Nigerian English was low; where the differences lie minimally in the utterances with falling pitch and appear significantly with the rising tone. Akinjobi and Oladipupo (2010) also looked at the place of intonation as not only being that which is said but how it is said, investigating the intonation and attitude in Nigerian English with the intention of ascertaining the extent to which Nigerian speakers of English use English intonation tunes to express attitudes. A level of deficiency in the use of intonation was recorded among the respondents.…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the other hand are the proponents of an exonormative accent (e.g. Akinjobi, 2012aAkinjobi, , 2020Adesanya, 2020;Awonusi, 2020) who opine that retaining RP is the more viable option in view of the multiple English accents in Nigeria and the need to maintain intelligibility with other speakers of English around the world. They argue that, since RP is defined and codified, learning materials (e.g.…”
Section: English Pronunciation and Modelling Issues In Nigeriamentioning
confidence: 99%
“…However, a few others are of the opinion that the exonormative Standard (RP) should be upheld in order to sustain intelligibility with other English speakers worldwide. But in the absence of native English models, an acrolectal variety that is close to RP or technology-driven, non-enculturation sources of speech practice should be adopted as a normative model (Akinjobi, 2012a;Awonusi, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations